Analysis Juridical Follow Criminal Trafficking in Persons ( Law Number 21 of 2007 Concerning Eradication Follow Criminal Trafficking in Persons) - Sudiarni Sudiarni; Nadiana Nadiana; Elvina Safitri (PT. Publikasiku Academic Solution, 2022)
Background: Phenomenon human trafficking already often happened in Indonesia , especially in Tanjungpinang City . Trading this person is something form practice crime that violates honor and dignity humans , as well is violation to right basic human . Follow criminal human trafficking is very troubling society , so need existence serious action _ from government for cope act criminal this person trade . Trading this person no only there is a problem in one country only , but already plunge into the cross country or international . Aim: For analyze _ juridical act criminal trafficking in persons ( Law Number 21 of 2007 concerning Eradication Follow Criminal Trafficking in Persons). Methods: Method used _ is method Qualitative with use study normative juridical . Findings: government publish Law No. 21 of 2007 concerning Eradication Follow Criminal Trafficking in Persons. Regulation the expected could give legal protection _ direct nor no direct to society . Law No. 21 of 2007 concerning Eradication Follow Criminal Human Trafficking mentions that Everyone who is a victim of human trafficking has the right for get restitution. However , so birth Constitution this feel not yet fulfill the sense of justice to people who are victims of this person trade